Heavy duty tire
The heavy-duty tire design with a specific rubber composition and carbon black ratio in the cap tread layer addresses adhesion issues, ensuring excellent braking, wear resistance, and fuel efficiency while suppressing static electricity.
Patent Information
- Application Number
- JP2023101493
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Heavy-duty tires face challenges in maintaining excellent braking performance, wear resistance, and fuel efficiency while incorporating a conductive portion to suppress static electricity, as adhesion issues between different rubber components can lead to cracks and reduced durability.
A heavy-duty tire design featuring a cap tread layer composed of a first tread rubber and a second tread rubber, where the first rubber contains isoprene and specific fillers, and the second rubber has a carbon black composition that satisfies a volume fraction to Stokes diameter ratio, ensuring continuous extension and localized arrangement to enhance adhesion and performance.
The tire achieves improved braking performance, wear resistance, and fuel efficiency while suppressing static electricity, with the second tread rubber effectively preventing cracks and enhancing antistatic effects.
Smart Images

Figure 2025001802000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a heavy duty tire including a tread portion having a conductive portion (earth tread) for suppressing static electricity. [Background technology]
[0002] Tires (heavy-duty tires) used on vehicles such as trucks and buses are subject to a larger load than passenger vehicle tires, so it is important that they have excellent braking performance and wear resistance. On the other hand, with increasing interest in global environmental issues, environmental regulations for heavy-duty tires are also becoming stricter, and further improvements in fuel efficiency are required. For this reason, for example, Patent Document 1 proposes blending silica into a rubber component mainly made of natural rubber and blending a specific silane coupling agent to improve the dispersion of silica and improve fuel efficiency in addition to wear resistance.
[0003] On the other hand, attempts have been made to replace a part of the cap tread rubber constituting the tire contact surface with another rubber having different physical properties, thereby adding tire performance based on the physical properties of the other rubber. For example, in Patent Document 2, a conductive part (so-called earth tread) made of conductive rubber that penetrates the cap tread and is exposed to the tire contact surface is provided in a part of the cap tread in the tire width direction. A tire equipped with such a conductive part (earth tread) can release static electricity generated on a vehicle while the vehicle is traveling from the belt layer to the road surface via the conductive part (earth tread), thereby suppressing the charging of the vehicle.
[0004] However, when replacing a part of the cap tread rubber with another rubber having different physical properties as described above, if the adhesion between the rubber constituting the main part of the cap tread rubber and the other rubber cannot be ensured, cracks may occur at the interface between these rubbers, which may cause abnormal appearance or reduce the durability of the tire. Therefore, it has been difficult to ensure the excellent braking performance and wear resistance required for heavy-duty tires while replacing a part of the cap tread rubber with another rubber having different physical properties (e.g., earth tread) in the above-mentioned heavy-duty tires. Therefore, there is a demand for measures to suppress the occurrence of cracks between these rubbers and improve braking performance, wear resistance, and fuel efficiency while exerting performance based on the rubber physical properties of the cap tread rubber composed of multiple rubbers (e.g., anti-static effect). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-056068 A [Patent Document 2] JP 2019-018725 A Summary of the Invention [Problem to be solved by the invention]
[0006] The object of the present invention is to provide a heavy-duty tire that exhibits performance based on the physical properties of each rubber of a cap tread rubber composed of multiple rubbers, while suppressing the occurrence of cracks between these rubbers and improving wear resistance and fuel efficiency. [Means for solving the problem]
[0007] The heavy-duty tire of the present invention for achieving the above object is a heavy-duty tire having a tread portion extending in a tire circumferential direction to form an annular shape, the cap tread layer constituting the tread portion is composed of a first tread rubber and a second tread rubber, the first tread rubber and the second tread rubber each constitute a tire contact surface so as to extend continuously in the tire circumferential direction, the second tread rubber is locally disposed in a part of the first tread rubber in the tire width direction, the cross-sectional area of the second tread rubber in the tire meridian cross section is 0.1% to 3% of the cross-sectional area of the cap tread layer, and the first tread rubber contains 50% by mass or more of isoprene-based rubber. The second tread rubber is made of a first rubber composition in which less than 35 parts by mass of a first carbon black and 20 parts by mass or more of silica are blended as fillers per 100 parts by mass of a rubber component having a rubber composition having a diameter of 100 mm or less, and the total amount of the fillers is 75 parts by mass or less per 100 parts by mass of the rubber component; the second tread rubber is made of a second rubber composition in which a second carbon black having a Stokes diameter D2 [nm] is blended into the rubber component; the volume fraction φ2 [%] of the second carbon black in the second rubber composition is 15% to 22%, and the volume fraction φ2 [%] and the Stokes diameter D2 [nm] of the second carbon black satisfy the relationship φ2 / D2≧0.14. Effect of the Invention
[0008] The cap tread rubber of the heavy duty tire of the present invention is composed of the first tread rubber and the second tread rubber as described above, and since these first tread rubber and the second tread rubber have the above-mentioned composition and characteristics, it is possible to ensure excellent braking performance, wear resistance and fuel efficiency due to the first tread rubber, while exhibiting the static electricity suppression effect due to the second tread rubber, and suppressing the occurrence of cracks at the interface between the first tread rubber and the second tread rubber, thereby achieving a high degree of compatibility between these performances.
[0009] In the present invention, the nitrogen adsorption specific surface area N2SA of the second carbon black is 40 m 2 / g~120m 2 / g. Also, it is preferable that the second rubber composition contains oil and resin, and the total amount of the oil and resin per 100 parts by mass of the rubber component is 15 parts by mass or more. This is advantageous in suppressing cracking at the interface between the first tread rubber and the second tread rubber while exerting the static electricity suppression effect of the second tread rubber, and in improving wear resistance and fuel economy.
[0010] In the present invention, it is preferable that the total amount of filler blended in the first rubber composition is 50 to 75 parts by mass relative to 100 parts by mass of the rubber component, the silica ratio in the filler is 40% by mass or more, and the volume fraction φ1 [%] of the first carbon black in the first rubber composition and the Stokes diameter D1 [nm] of the first carbon black satisfy the relationship φ1 / D1<0.13. This is advantageous in improving the wear resistance and fuel efficiency of the first tread rubber and suppressing the occurrence of cracks at the interface between the first tread rubber and the second tread rubber.
[0011] In the present invention, the volume fraction (φ1, φ2) of carbon black is a value (unit: %) calculated as the ratio (A / B) of volume A to volume B, based on volume A calculated by dividing the compounding weight of carbon black compounded in each rubber composition by its specific gravity and volume B calculated as the sum of the volumes of each material calculated by dividing the compounding weight of each of all compounding ingredients in a rubber composition for tires by the specific gravity of each ingredient. The Stokes diameter (D1, D2) of carbon black is the mode diameter Dst (unit: nm), which is the maximum value in the mass distribution curve of the Stokes diameter of the carbon black aggregates compounded in each rubber composition, and is measured in accordance with the method for determining aggregate distribution by disk centrifuge photosedimentation method of JIS K6217-6.
[0012] The heavy duty tire of the present invention is preferably a pneumatic tire, but may also be a non-pneumatic tire. In the case of a pneumatic tire, the inside of the tire can be filled with air, an inert gas such as nitrogen, or other gases. [Brief description of the drawings]
[0013] [Figure 1] 1 is a meridian cross-sectional view showing an example of a heavy duty tire of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The configuration of the present invention will be described in detail below with reference to the accompanying drawings.
[0015] When the heavy-duty tire of the present invention is a pneumatic tire as shown in Fig. 1, it comprises a tread portion 1 that contacts the road surface, a pair of sidewall portions 2 arranged on both sides of the tread portion 1, and a pair of bead portions 3 arranged on the tire radial inner side of the sidewall portions 2. In Fig. 1, the symbol CL indicates the tire equator. Although not depicted in Fig. 1 because it is a meridian cross section, the tread portion 1, the sidewall portions 2, and the bead portions 3 each extend in the tire circumferential direction to form an annular shape, thereby forming a basic toroidal structure of a pneumatic tire. The following description using Fig. 1 is basically based on the meridian cross section shown in the figure, but each tire component extends in the tire circumferential direction to form an annular shape.
[0016] A carcass layer 4 is installed between a pair of left and right bead portions 3. This carcass layer 4 includes a plurality of reinforcing cords extending in the tire radial direction, and is folded back from the inside to the outside in the tire width direction around a bead core 5 arranged in each bead portion 3. In addition, a bead filler 6 is arranged on the outer periphery of the bead core 5, and this bead filler 6 is sandwiched between the main body portion and the folded back portion of the carcass layer 4.
[0017] A plurality of belt layers 7 (four layers in FIG. 1) are embedded on the outer circumferential side of the carcass layer 4 in the tread portion 1. Each belt layer 7 includes a plurality of reinforcing cords (steel cords) oriented in a predetermined direction. The plurality of belt layers 7 may include a cross belt pair. The cross belt pair is a combination of at least two belt layers in which the inclination angle of the reinforcing cords with respect to the tire circumferential direction is set in the range of 10° to 40°, and the inclination direction of the reinforcing cords is reversed between the layers so that the reinforcing cords cross each other. In addition to the cross belt pair, a high-angle belt layer in which the inclination angle of the reinforcing cords with respect to the tire circumferential direction is set in the range of 40° to 70°, a protective belt layer arranged in the outermost layer and having a width of 85% or less of the other belt layers, a circumferential reinforcing layer in which the angle of the reinforcing cords with respect to the tire circumferential direction is set in the range of 0° to 5°, and the like may be optionally provided. For example, in FIG. 1, one protective belt layer is arranged in the outermost layer, one high-angle belt layer is arranged in the innermost layer, and the other two layers are cross belt pairs. Furthermore, a belt reinforcing layer (not shown) may be provided on the outer circumferential side of the belt layer 7. The belt reinforcing layer may be made of, for example, organic fiber cords oriented in the tire circumferential direction. The organic fiber cords constituting the belt reinforcing layer 8 may be set at an angle of, for example, 0° to 5° with respect to the tire circumferential direction.
[0018] A tread rubber layer 10 is disposed on the outer peripheral side of the carcass layer 4 in the tread portion 1, a side rubber layer 20 is disposed on the outer peripheral side (outside in the tire width direction) of the carcass layer 4 in the sidewall portion 2, and a rim cushion rubber layer 30 is disposed on the outer peripheral side (outside in the tire width direction) of the carcass layer 4 in the bead portion 3. The tread rubber layer 10 has a structure in which two types of rubber layers with different physical properties (a cap tread layer 11 that forms the tread surface of the tread portion 1 and an under tread layer 12 disposed on its inner peripheral side) are laminated in the tire radial direction.
[0019] Since the present invention mainly relates to the cap tread layer 11, as long as the tread portion 1 (tread rubber layer 10) is composed of the cap tread layer 11 and the under tread layer 12, the basic structure of the other parts is not limited to the above-mentioned structure.
[0020] The cap tread layer 11 of the present invention is composed of a first tread rubber C1 and a second tread rubber C2. The first tread rubber C1 and the second tread rubber C2 each form a tire contact surface so as to extend continuously in the tire circumferential direction. In FIG. 1, the first tread rubber C1 forms a main part of the cap tread layer 11, and the second tread rubber C2 (the shaded part in the figure) is locally arranged in a part of the first tread rubber C1 in the tire width direction. In particular, when the second tread rubber C2 is a rubber that functions as a so-called earth tread, the second tread rubber C2 is preferably provided so as to penetrate the tread rubber layer 10 and reach the belt layer 7 from the tread surface, taking into consideration the path for discharging static electricity to the road surface.
[0021] The first tread rubber of the present invention constitutes the main part of the cap tread layer 11 as described above, and the rubber component is a diene rubber, which necessarily contains an isoprene rubber. In addition, it may contain a butadiene rubber or a styrene-butadiene rubber as an option.
[0022] Examples of the isoprene-based rubber used in the first tread rubber include various natural rubbers, epoxidized natural rubbers, and various synthetic polyisoprene rubbers. As the isoprene-based rubber, rubbers that are usually used in rubber compositions for tires can be used. The content of the isoprene-based rubber is 50% by mass or more, preferably 60% by mass to 80% by mass, when the total diene-based rubber is taken as 100% by mass. By containing a specific amount of the isoprene-based rubber in this way, it is possible to achieve a good balance between wear resistance and fuel economy. If the content of the isoprene-based rubber is less than 50% by mass, chipping resistance is deteriorated.
[0023] The first tread rubber is necessarily compounded with a filler containing silica. The first tread rubber containing silica as a filler is advantageous in improving fuel economy performance. As described above, the filler necessarily contains silica, but other fillers can also be compounded. Examples of other fillers include carbon black, calcium carbonate, magnesium carbonate, talc, clay, alumina, aluminum hydroxide, titanium oxide, and calcium sulfate. These other fillers may be used alone or in combination of two or more. Among these other fillers, carbon black can be preferably used. That is, it is preferable to use silica and carbon black in combination as a filler.
[0024] The amount of the filler used in the first tread rubber (when the first carbon black and silica are used as described later, the total amount of the first carbon black and silica) is 75 parts by mass or less, preferably 50 parts by mass to 75 parts by mass, and more preferably 55 parts by mass to 70 parts by mass, per 100 parts by mass of the diene rubber. If the amount of the filler exceeds 75 parts by mass, heat generation and processability are reduced. If the amount of the filler is set within the above-mentioned preferred range or a more preferred range, the difference in physical properties with the second tread rubber described later can be suppressed, which is advantageous in terms of improving wear resistance (suppressing the difference in wear between the first tread rubber and the second tread rubber).
[0025] The silica necessarily contained in the filler used in the first tread rubber may be any silica normally used in rubber compositions for tires. For example, wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), calcium silicate, aluminum silicate, etc. may be mentioned, and these may be used alone or in combination of two or more kinds.
[0026] The content of silica in the filler used in the first tread rubber is 40% by mass or more, preferably 45% to 99% by mass, when the entire filler is 100% by mass. If the content of silica is less than 40% by mass, the effect of improving fuel economy is limited. The amount of silica alone is 20 parts by mass or more, preferably 50 parts by mass or more, per 100 parts by mass of the rubber component constituting the first tread rubber. In this way, the first tread rubber contains a sufficient amount of silica, which can further improve fuel economy. If the amount of silica is less than 20 parts by mass, the effect of improving fuel economy is limited.
[0027] The CTAB adsorption specific surface area of the silica used in the first tread rubber is not particularly limited, but is preferably 120 m 2 / g or more, more preferably 140m 2 / g~230m 2 / g, more preferably 140m 2 / g~175m 2 / g. The CTAB adsorption specific surface area of silica is 120 m 2 When the specific surface area is less than 1 / g, the effect of improving the wear resistance and low rolling resistance may not be sufficiently obtained. In this specification, the CTAB adsorption specific surface area of silica is a value measured according to ISO 5794.
[0028] In the first tread rubber, it is preferable to compound a silane coupling agent together with silica. By compounding the silane coupling agent, the dispersibility of silica in the rubber component can be improved, and abrasion resistance and fuel economy performance can be improved in a well-balanced manner.
[0029] The type of silane coupling agent is not particularly limited as long as it can be used in a rubber composition containing silica. Examples of the silane coupling agent include sulfur-containing silane coupling agents such as bis-(3-triethoxysilylpropyl) tetrasulfide, bis(3-triethoxysilylpropyl) disulfide, 3-trimethoxysilylpropyl benzothiazole tetrasulfide, γ-mercaptopropyl triethoxysilane, and 3-octanoylthiopropyl triethoxysilane.
[0030] When the silane coupling agent is blended in the first tread rubber, the blending amount is not particularly limited, but is preferably 1% by mass to 20% by mass, more preferably 5% by mass to 15% by mass, based on the blending amount of the silica. If the blending amount of the silane coupling agent is less than 1% by mass of the silica blending amount, the dispersion of the silica cannot be sufficiently improved. If the blending amount of the silane coupling agent is more than 20% by mass of the silica blending amount, the silane coupling agent condenses with itself, and the desired tensile strength of the rubber composition cannot be obtained.
[0031] The filler used in the first tread rubber necessarily contains silica as described above, but preferably further contains carbon black (sometimes referred to as "first carbon black" to distinguish it from the carbon black compounded in the second tread rubber described later). When carbon black is used in combination, the nitrogen adsorption specific surface area N2SA of the first carbon black is preferably 65 m 2 / g or more, more preferably 65m 2 / g~120m 2 / g, more preferably 65m 2 / g~100m 2 / g. In this way, the use of carbon black with an appropriate particle size is advantageous in improving wear resistance. The nitrogen adsorption specific surface area N2SA of the first carbon black is 65 m 2 If the nitrogen adsorption specific surface area N2SA of carbon black is less than 1 / g, the effect of improving abrasion resistance cannot be expected to be sufficient. The nitrogen adsorption specific surface area N2SA of carbon black is measured in accordance with JIS K6217-2.
[0032] The amount of the first carbon black is preferably 60% by mass or less, more preferably 1% by mass to 55% by mass, when the entire filler used in the first tread rubber is taken as 100% by mass. The amount of the first carbon black alone is less than 35 parts by mass, preferably 15 parts by mass to 30 parts by mass, per 100 parts by mass of the rubber component constituting the first tread rubber. If the amount of the first carbon black is 35 parts by mass or more per 100 parts by mass of the rubber component, there is a risk of low fuel consumption. Similarly, if the amount of the first carbon black is more than 60% by mass per 100% by mass of the filler, there is a risk of low fuel consumption.
[0033] In the first tread rubber, it is preferable to compound a guanidine-based vulcanization accelerator as a vulcanization accelerator. Examples of the guanidine-based vulcanization accelerator include diphenyl guanidine, di(o-tolyl)guanidine, and o-tolyl bigianide. The compounding amount of the guanidine-based vulcanization accelerator is preferably 0.1 parts by mass or more, more preferably 0.4 to 1.5 parts by mass, per 100 parts by mass of the diene rubber. In this way, the first tread rubber contains a sufficient amount of a specific vulcanization accelerator, which is advantageous for improving wear resistance and fuel efficiency. If the compounding amount of the guanidine-based vulcanization accelerator is less than 0.1 parts by mass, it becomes difficult to ensure an appropriate vulcanization speed.
[0034] The second tread rubber forms the tire ground contact surface together with the first tread rubber, but is different from the first tread rubber constituting the main part of the cap tread layer 11, and is provided partially in a part of the tire width direction in order to add a specific function (for example, antistatic effect) to the cap tread layer 11. In such a second tread rubber, the type of rubber component is not particularly limited, and diene rubbers generally used in rubber compositions for tires, such as natural rubber, butadiene rubber, isoprene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, butyl rubber, and halogenated butyl rubber, can be used. These diene rubbers may be terminal-modified rubbers. These diene rubbers can be used alone or as an arbitrary blend. The rubber component constituting the second tread rubber may be appropriately selected depending on the function to be added by the second tread rubber, and in the case of the present invention, natural rubber, butadiene rubber, isoprene rubber, styrene-butadiene rubber, and the like can be suitably used among the various rubbers mentioned above.
[0035] In the second tread rubber, carbon black (sometimes referred to as "second carbon black" to distinguish it from the carbon black blended in the first tread rubber) is always blended as a filler. By blending carbon black in this way, it is possible to improve abrasion resistance. The blending amount of the second carbon black is preferably 40 parts by mass or more, more preferably 45 to 65 parts by mass, per 100 parts by mass of the rubber component constituting the second tread rubber. If the blending amount of the second carbon black is less than 40 parts by mass, the abrasion resistance decreases.
[0036] The second tread rubber may contain silica as a filler. However, when the second tread rubber contains silica, the compounding amount is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the rubber component. If the compounding amount of silica exceeds 15 parts by mass, the antistatic effect is reduced.
[0037] The second tread rubber may contain other fillers in addition to the above-mentioned second carbon black and silica. Examples of the other fillers include calcium carbonate, magnesium carbonate, talc, clay, alumina, aluminum hydroxide, titanium oxide, and calcium sulfate. These other fillers may be used alone or in combination of two or more.
[0038] The type of the second carbon black is not particularly limited, but the nitrogen adsorption specific surface area N2SA is preferably 40 m 2 / g~120m 2 / g, more preferably 65m 2 / g~120m 2 / g, more preferably 65m 2 / g~100m 2 / g. Using carbon black with an appropriate particle size is advantageous for improving wear resistance. The nitrogen adsorption specific surface area N2SA of the second carbon black is preferably 40 m 2 If the nitrogen adsorption specific surface area N2SA of the second carbon black is less than 120 m 2 If it exceeds 1 / g, the compression strength between the first tread rubber and the second tread rubber during extrusion may decrease, which may result in a decrease in cornering durability. The nitrogen adsorption specific surface area N2SA of carbon black is measured in accordance with JIS K6217-2.
[0039] When the second carbon black is compounded, the volume fraction φ2 [%] of the second carbon black in the second rubber composition is set to 15% to 22%, preferably 18% to 21%. The volume fraction φ2 [%] of the second carbon black in the second rubber composition and the Stokes diameter D2 [nm] of the second carbon black are set to satisfy the relationship of φ2 / D2≧0.14, preferably 0.16≦φ2 / D2≦0.21. The inventor of the present invention has studied the compounding and physical properties of the rubber composition constituting the second tread rubber in introducing the second tread rubber (particularly the earth tread rubber with the static electricity suppression effect) into the tread portion, and has found that there is a correlation between the static electricity suppression effect and the ratio φ2 / D2, thereby arriving at the present invention. That is, the present invention improves the charge suppression effect without impairing the tire performance required for heavy-duty tires by setting the volume fraction φ2 [%] of the second carbon black blended in the second rubber composition and the ratio φ2 / D2 of this volume fraction φ2 [%] and the Stokes diameter D2 [nm] within the above-mentioned range. At this time, if the volume fraction φ2 is less than 15%, the abrasion resistance is deteriorated. If the volume fraction φ2 exceeds 22%, the fuel economy performance and crack resistance are deteriorated. If the ratio φ2 / D2 is less than 0.14, the abrasion resistance is reduced.
[0040] In addition, when the ratio φ2 / D2 is set for the second tread rubber as described above, the ratio of the volume fraction of the first carbon black to the Stokes diameter may be set for the first tread rubber (first rubber composition) in the same manner. Specifically, the volume fraction φ1 [%] of the first carbon black blended in the first rubber composition and the Stokes diameter D1 [nm] of the first carbon black preferably satisfy the relationship φ1 / D1<0.13, more preferably 0.05≦φ1 / D1≦0.12. By setting the ratio φ1 / D1 in this manner, the fuel economy performance can be improved. If the ratio φ1 / D1 is 0.10 or more, the effect of improving the fuel economy performance becomes limited.
[0041] It is preferable to blend oil and resin in the second tread rubber. Blending oil and resin improves the adhesion of the second tread rubber to the first tread rubber, which is advantageous for improving tire durability. Examples of oil include process oil and paraffin oil, and among them, process oil is preferably used. Examples of resin include petroleum-based resin and phenolic resin, and among them, petroleum-based resin is preferably used. The total blending amount of oil and resin is 15 parts by mass or more, preferably 15 to 25 parts by mass, per 100 parts by mass of the rubber component constituting the second tread rubber. If the blending amount of oil and resin is less than 15 parts by mass, the effect of improving the adhesion described above cannot be expected sufficiently. The blending amount of each of the oil and resin is not particularly limited, but the oil may be blended in an amount of, for example, 10 to 15 parts by mass per 100 parts by mass of the rubber component, and the resin may be blended in an amount of, for example, 1.0 to 5.0 parts by mass per 100 parts by mass of the rubber component.
[0042] In the tire, the second tread rubber is provided locally in a part of the cap tread layer as described above. In this case, the cross-sectional area of the second tread rubber in the tire meridian section is preferably set to 0.1% to 3%, more preferably 0.5% to 2% of the cross-sectional area of the cap tread layer. This allows the first tread rubber and the second tread rubber to be arranged in a well-balanced manner in the tire (cap tread layer), and it is possible to highly achieve both the low fuel consumption performance provided by the first tread rubber and the effect added by the second tread rubber (for example, the static electricity suppression effect).
[0043] The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to these examples. EXAMPLES
[0044] Cap tread rubbers (Standard Example 1, Comparative Examples 1 to 8, Examples 1 to 5) composed of a first tread rubber and a second tread rubber having the compositions and physical properties shown in Tables 1 to 4 were extrusion molded, and test tires (tire size: 11R22.5) having a cap tread layer composed of these cap tread rubbers and the basic structure shown in Figure 1 were manufactured.
[0045] In addition, the table shows the volume fractions φ1, φ2 of carbon black in the rubber composition and the ratio (φ1 / D1, φ2 / D2) of the volume fractions (φ1, φ2) and the Stokes diameters (D1, D2) of carbon black for each of the first tread rubber and the second tread rubber. The volume fractions (φ1, φ2) of carbon black were calculated as the ratio (A / B) of the volume A to the volume B, based on the volume A calculated by dividing the compounding weight of carbon black compounded in each rubber composition by the raw material specific gravity and the total volume B calculated by dividing the compounding weight of each of the compounding ingredients in the rubber composition for tires by the raw material specific gravity, [unit: %]. The Stokes diameters (D1, D2) of carbon black are the mode diameters Dst [unit: nm], which are the maximum values in the mass distribution curve of the Stokes diameters of the aggregates of carbon black compounded in each rubber composition, and were measured in accordance with the method for determining aggregate distribution by the disk centrifuge photosedimentation method of JIS K6217-6. Table 3 shows the materials commonly compounded in the first tread rubber. Table 4 shows the compounding, volume fraction φ2, and ratio φ2 / D2 of each of the second tread rubbers (A to F) used, and Tables 1 and 2 show the type of second tread rubber (symbols A to F) used in each example.
[0046] Each test tire was used to evaluate cornering durability, wear resistance, fuel economy, and antistatic performance by the methods described below.
[0047] Cornering durability Each test tire was mounted on a wheel with a rim size of 22.5 x 9.0, and the air pressure was set to 830 kPa before being mounted on a test vehicle, and the presence or absence of cracks occurring at the interface between the first tread rubber and the second tread rubber after driving 50,000 km on dry roads was checked. The evaluation results were indicated as "unacceptable" when cracks occurred, and "good" when no cracks occurred.
[0048] Abrasion resistance Each test tire was mounted on a wheel with a rim size of 22.5 x 9.0, and driven 20,000m using a drum testing machine with a drum diameter of 1707 mm under conditions of a load of 29.42 kN, air pressure of 830 kPa, and speed of 50 km / h. The difference in the amount of wear between the first tread rubber and the second tread rubber after the run was measured. The evaluation results were shown on a five-point scale. A score of "4" or higher indicates sufficient wear resistance, and a higher score indicates better high-speed durability. 5: Difference in wear is 0 mm or more and 0.2 mm or less 4: Difference in wear is more than 0.2 mm and less than 0.5 mm 3: Difference in wear is more than 0.5 mm and less than 1.0 mm 2: Difference in wear is more than 1.0 mm and less than 1.5 mm 1: The difference in wear is more than 1.5 mm
[0049] Low fuel consumption Each test tire was mounted on a wheel with a rim size of 22.5 x 9.0, and the reciprocal of the rolling resistance coefficient of the test tire was calculated using a drum testing machine with a drum diameter of 1707 mm in accordance with ISO28580 under the conditions of a load of 28.76 kN, an air pressure of 900 kPa, and a speed of 60 km / h. The evaluation results were expressed as an index using the reciprocal of the measured value, with standard example 1 being 100. The higher the index value, the lower the rolling resistance and the better the fuel efficiency performance. An index value of 98 or more means that excellent fuel efficiency performance equivalent to that of standard example 1 was obtained.
[0050] Static charge suppression performance The electrical resistance value of each cap tread rubber was measured in accordance with JIS K6911. The evaluation results were expressed as an index using the reciprocal of the measured value, with Comparative Example 1 being 100. The larger the index value, the smaller the electrical resistance value and the more excellent the antistatic performance. Note that since Standard Example 1 does not have a second tread rubber (earth tread) and does not have antistatic performance, the antistatic performance was not evaluated.
[0051] [Table 1]
[0052] [Table 2]
[0053] [Table 3]
[0054] [Table 4]
[0055] The types of raw materials used in Tables 1 to 3 are shown below. [First tread rubber] NR: Natural rubber, RSS No.3 SBR: Styrene butadiene rubber, Zeon Nipol 1502 CB: Carbon black (grade: ISAF), Niteron #300IH (nitrogen adsorption specific surface area NSA: 115m 2 / g) Silica: Solvay Zeosil 1165MP (CTAB adsorption specific surface area: 156 m 2 / g) Silane coupling agent: Bis(3-triethoxysilylpropyl)tetrasulfide, Si69 manufactured by Evonik Degussa Japan Zinc oxide: Three types of zinc oxide manufactured by Seido Chemical Industry Co., Ltd. Wax: Sannock manufactured by Ouchi Shinko Chemical Co., Ltd. Stearic acid: NOF Corporation YR stearic acid Anti-aging agent: Santoflex 6PPD manufactured by Solutia Europe Vulcanization accelerator: Sulfenamide vulcanization accelerator, Noccela CZ-G manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Sulfur: Oil-treated sulfur manufactured by Karuizawa Refinery
[0056] The types of raw materials used in Table 4 are shown below. [Second tread rubber] NR: Natural rubber, RSS No.3 SBR: Styrene butadiene rubber, Zeon Nipol 1502 CB1: Carbon black (grade: ISAF), Niteron #300IH (Dst: 83 nm, nitrogen adsorption specific surface area N2SA: 115 m 2 / g) CB2: Carbon black (grade: HAF), Niteron #200IN manufactured by Nippon Steel Carbon Co., Ltd. (Dst: 114 nm, nitrogen adsorption specific surface area N2SA: 72 m 2 / g) CB3: Carbon black (grade: FEF), Nitelon #10N manufactured by Nippon Steel Carbon Co., Ltd. (Dst: 166nm, nitrogen adsorption specific surface area N2SA: 41m 2 / g) Process oil: Shell Lubricants Japan Co., Ltd. Extract No. 4 S Resin: A mixture of maleic acid modified rosin and petroleum resin, Haritac AQ-90A manufactured by Harima Chemicals Zinc oxide: Three types of zinc oxide manufactured by Seido Chemical Industry Co., Ltd. Wax: Sannock manufactured by Ouchi Shinko Chemical Co., Ltd. Stearic acid: NOF Corporation YR stearic acid Anti-aging agent: Santoflex 6PPD manufactured by Solutia Europe Vulcanization accelerator: Sulfenamide vulcanization accelerator, Noccela CZ-G manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Sulfur: Oil-treated sulfur manufactured by Karuizawa Refinery
[0057] As is clear from Tables 1 and 2, Examples 1 to 5 maintained or improved the cornering durability, wear resistance, and fuel economy performance compared to Standard Example 1, while also improving the static electricity suppression performance compared to Comparative Example 1.
[0058] On the other hand, in Comparative Example 1, the ratio φ2 / D2 of carbon black in the second tread rubber was small, so the abrasion resistance was reduced. In Comparative Example 2, the ratio of the cross-sectional area of the second tread rubber was small, so the static electricity suppression performance was not obtained. In Comparative Example 3, the ratio of the cross-sectional area of the second tread rubber was large, so the fuel economy performance was deteriorated. In Comparative Example 4, the volume fraction φ2 of carbon black in the second tread rubber was small, so the abrasion resistance was deteriorated. In Comparative Example 5, the volume fraction φ2 of carbon black in the second tread rubber was large, so the cornering durability and the fuel economy performance were deteriorated. In Comparative Example 6, the amount of isoprene-based rubber (natural rubber) in the first tread rubber was small, so the cornering durability was deteriorated. In Comparative Example 7, the amount of carbon black in the first tread rubber was large and the amount of silica in the first tread rubber was small, so the fuel economy performance was deteriorated. In Comparative Example 8, the total amount of filler was large, so the cornering durability, abrasion resistance, fuel economy performance, and static electricity suppression performance were deteriorated.
[0059] The present disclosure includes the following inventions. Invention [1] A heavy-duty tire having a tread portion extending in the tire circumferential direction and forming an annular shape, a cap tread layer constituting the tread portion is composed of a first tread rubber and a second tread rubber, the first tread rubber and the second tread rubber each constitute a tire contact surface so as to extend continuously in a tire circumferential direction, the second tread rubber is locally disposed in a part of the first tread rubber in the tire width direction, and a cross-sectional area of the second tread rubber in a tire meridian cross section is 0.1% to 3% of a cross-sectional area of the cap tread layer, The first tread rubber is made of a first rubber composition in which less than 35 parts by mass of a first carbon black and 20 parts by mass or more of silica are blended as fillers with 100 parts by mass of a rubber component containing 50% by mass or more of an isoprene-based rubber, and the total blending amount of the fillers is 75 parts by mass or less with respect to 100 parts by mass of the rubber component, The second tread rubber is made of a second rubber composition in which a rubber component is blended with a second carbon black having a Stokes diameter D2 [nm], a volume fraction φ2 [%] of the second carbon black in the second rubber composition is 15% to 22%, and the volume fraction φ2 [%] and the Stokes diameter D2 [nm] of the second carbon black satisfy the relationship φ2 / D2≧0.14. Invention [2] The nitrogen adsorption specific surface area N2SA of the second carbon black is 40 m 2 / g~120m 2 / g. Invention [3] A heavy-duty tire according to invention [1] or [2], characterized in that the second rubber composition is blended with oil and resin, and the total amount of the oil and the resin blended per 100 parts by mass of the rubber component is 15 parts by mass or more. Invention [4] A heavy-duty tire according to any one of inventions [1] to [3], characterized in that a total amount of the filler blended in the first rubber composition is 50 parts by mass to 75 parts by mass per 100 parts by mass of a rubber component, a silica ratio in the filler is 40 mass% or more, and a volume fraction φ1 [%] of the first carbon black in the first rubber composition and a Stokes diameter D1 [nm] of the first carbon black satisfy a relationship of φ1 / D1<0.13. [Explanation of symbols]
[0060] 1 Tread section 2 Sidewall 3 Bead section 4 Carcass layer 5 Bead Core 6 Bead Filler 7 Belt layer 8 Belt reinforcement layer 10 Tread rubber layer 11 Cap tread layer 12 Undertread layer C1 First tread rubber C2 Second tread rubber 20 Side rubber layer 30 Rim cushion rubber layer CL Tire Equator
Claims
1. A heavy-duty tire having a tread portion extending in a circumferential direction of the tire and forming an annular shape, a cap tread layer constituting the tread portion is composed of a first tread rubber and a second tread rubber, the first tread rubber and the second tread rubber each constitute a tire contact surface so as to extend continuously in a tire circumferential direction, the second tread rubber is locally disposed in a part of the first tread rubber in the tire width direction, and a cross-sectional area of the second tread rubber in a tire meridian cross section is 0.1% to 3% of a cross-sectional area of the cap tread layer, The first tread rubber is made of a first rubber composition in which less than 35 parts by mass of a first carbon black and 20 parts by mass or more of silica are blended as fillers with 100 parts by mass of a rubber component containing 50% by mass or more of an isoprene-based rubber, and the total blending amount of the fillers is 75 parts by mass or less with respect to 100 parts by mass of the rubber component, The second tread rubber is made of a second rubber composition in which a second carbon black having a Stokes diameter D2 [nm] is blended into a rubber component, a volume fraction φ2 [%] of the second carbon black in the second rubber composition is 15% to 22%, and the volume fraction φ2 [%] and the Stokes diameter D2 [nm] of the second carbon black satisfy the relationship φ2 / D2≧0.
14.
2. The nitrogen adsorption specific surface area N of the second carbon black 2 SA is 40m 2 / g ~ 120m 2 2. The heavy duty tire according to claim 1, wherein the tensile strength is 1 / g.
3. 3. The heavy-duty tire according to claim 1, wherein the second rubber composition is blended with oil and a resin, and a total amount of the oil and the resin blended per 100 parts by mass of the rubber component is 15 parts by mass or more.
4. The heavy-duty tire according to claim 1 or 2, characterized in that a total amount of the filler blended in the first rubber composition is 50 parts by mass to 75 parts by mass per 100 parts by mass of a rubber component, a silica ratio in the filler is 40% by mass or more, and a volume fraction φ1 [%] of the first carbon black in the first rubber composition and a Stokes diameter D1 [nm] of the first carbon black satisfy a relationship of φ1 / D1<0.13.
Citation Information
Patent Citations
JP2019‐018725A
JP2019‐056068A